Corporate Social Responsibility: Does Religious Community Matter? - Yugang He; Wanting Tian (Religions, 2022)
Corporate social responsibility is crucial to the sustainability of a firm, yet its motivating forces remain obscure. Therefore, this paper uses 1130 listed firms over the period 2010–2021 as the sample to explore the effect of religious community on corporate social responsibility in China. Using a firm and year-fixed effects model for empirical analysis. The findings reveal that the number of religious communities around a firm within a radius of less than 10, 50, and 100 km all has a favorable influence on corporate social responsibility. Moreover, the results of heterogeneity analysis show that religious community has a smaller positive impact on corporate social responsibility in low-polluting firms than in high-polluting ones. Additionally, using the robustness test, it is conceivable to conclude that the findings presented in this study are reliable and robust. This paper contributes to and broadens the existing body of research on corporate social responsibility and religious community, which has significant ramifications for the importance of religious community in the conduct of business.